Comparative Efficacy of Intra-articular Platelet-Rich Plasma Versus Dextrose Prolotherapy for Pain Reduction and Functional Recovery in Knee Osteoarthritis: A Meta-Analysis of Randomised Controlled Trials - Bagus Bayu Pradnyana; Bagus Diva Indra Dharma (HM Publisher, 2026)
Background: Knee osteoarthritis (OA) is a primary cause of chronic pain and disability. Intra-articular platelet-rich plasma (PRP) and hypertonic dextrose prolotherapy are emerging regenerative therapies, yet their comparative and long-term effectiveness remain incompletely characterized. This meta-analysis quantifies their pooled effect on pain and function, prioritizing the head-to-head comparison of PRP versus prolotherapy. Methods: A systematic search of PubMed, Scopus, and Google Scholar (to July 2025) identified randomized and prospective comparative trials evaluating intra-articular PRP and/or prolotherapy in adults with Kellgren–Lawrence grade I–III knee OA. Pain and functional outcomes were extracted, and risk of bias was assessed using the Cochrane RoB 2 framework. Standardized mean differences (Hedges' g) were pooled using a restricted maximum likelihood random-effects model, alongside subgroup and small-study effect analyses. Results: Ten studies (n=855) were included. The mixed-comparator pooled estimate significantly favored the active therapies (Hedges' g = −0.948, 95% CI −1.725 to −0.171; p=0.022; I²=94.9%). Subgroup analyses revealed an effect size of g = −1.302 for PRP versus prolotherapy, g = −1.049 for prolotherapy versus inactive comparators, and g = −0.412 for PRP versus saline placebo. Differences between subgroups were not statistically significant (p=0.627). Egger regression indicated small-study effects (p=0.016). Conclusion: Both PRP and prolotherapy yield clinically meaningful improvements in knee OA pain and function. PRP demonstrates larger, more durable effects in direct comparisons, positioning it as the preferred regenerative option for sustained benefit beyond six months. Prolotherapy remains a practical alternative for shorter-term relief. However, substantial heterogeneity, small-study effects, and modest advantages over blinded saline necessitate cautious translational interpretation.